The population structure of Beijing family of Mycobacterium tuberculosis in Western Siberia - A. A. Vyazovaya; O. A. Pasechnik; A. A. Gerasimova; I. V. Mokrousov (Туберкулез и болезни лёгких)
The objective: to study the structure of Beijing genotype family of Mycobacterium tuberculosis in Omsk Region, Western Siberia.Subjects and methods: 325 strains of M. tuberculosis were studied, all of them were isolated from tuberculosis patients in Omsk Region. Strains were tested to identify if they belonged to Beijing genotype, B0/W148 and 94-32. Locus NTF and region RD181 were assessed. Ancient Beijing strains were analyzed by spoligotyping and MIRU-VNTR-typed at 12 loci, and the obtained profiles were compared with the international database of SITVIT_WEB.Results. Among 204 (62.7%) strains of M. tuberculosis from Beijing family, 176 (86.3%) of strains belonged to the modern sublineage of 94-32 (60.7%) and B0/W148 (25.0%) clusters. Inside 94-32 cluster, it was found that 13 (10.5%) strains belonged to CAO group. Strains of the ancient Beijing sublineages of RD181[+] and RD181[-] were detected in 3.4% (7/204) and 10.3% (21/204) cases, respectively. All of Beijing RD181[+] strains had SIT269 spoligoprofile. The majority of strains of the ancient sublineage were represented by the MIRU types – MIT135 and MIT642.Conclusion. In Omsk Region of Western Siberia, strains of the modern sublineage prevail in the population of M. tuberculosis of Beijing family, the prevalence of ancient strains of this family is (13.7%). The high level of multiple drug resistance is typical of strains of the modern sublineage of B0/W148, 94-32 CAO clusters and strains of the ancient Beijing sublineage.